Sympathetic Pathways Target Cholinergic Neurons in the Human Colonic Myenteric Plexus - Parker, Dominic R.; Wiklendt, Lukasz; Humenick, Adam; Chen, Bao Nan; Sia, Tiong Cheng; Wattchow, David A.; Dinning, Phil G.; Brookes, Simon J. H. (Frontiers in Neuroscience, 2022)
Background The sympathetic nervous system inhibits human colonic motility largely by effects on enteric neurons. Noradrenergic axons, which branch extensively in the myenteric plexus, are integral to this modulatory role, but whether they contact specific types of enteric neurons is unknown. The purpose of this study was to determine the association of noradrenergic varicosities with types of enteric neurons. Methods Human colonic tissue from 7 patients was fixed and dissected prior to multi-layer immunohistochemistry for HuC/D (pan-neuronal cell body labelling), tyrosine hydroxylase (TH, catecholaminergic labelling), Enkephalin (ENK), choline acetyltransferase (ChAT, cholinergic labelling) and/or nitric oxide synthase (NOS, nitrergic labelling) and imaged using confocal microscopy. TH-immunoreactive varicose nerve endings and myenteric cell bodies were reconstructed as three dimensional digital images. Data was exported to a purpose-built software package which quantified the density of varicosities close to the surface of each myenteric cell body. Results TH-immunoreactive varicosities had a greater mean density within 1µm of the surface of ChAT+/NOS- nerve cell bodies compared with ChAT-/NOS+ cell bodies. Similarly, ENK-immunoreactive varicosities also had a greater mean density close to ChAT+/NOS- cell bodies compared with ChAT-/NOS+ cells. Conclusion A method for quantifying close associations between varicosities and nerve cell bodies was developed. Sympathetic axons in the myenteric plexus preferentially target cholinergic excitatory cells compared to nitrergic neurons (which are largely inhibitory). This connectivity is likely to be involved in inhibitory modulation of human colonic motility by the sympathetic nervous system.